(untitled) (The International Journal for Scientific Research, 2025)
This study explores the challenges faced by students with disabilities in higher education and the role of Universal Design for Learning (UDL) in creating more inclusive college environments. Students with disabilities encounter significant barriers that impact their academic performance and sense of belonging. These obstacles include faculty training, stigma surrounding disability disclosure, and limited awareness of available resources, however, this study mainly focus on accommodating students with disability in their physical space. The study employs a mixed-methods approach, combining a survey of students, faculty, and stakeholders with an analysis of architectural floor plans to identify areas for improvement in physical accessibility. The analysis of the floor plan, in accordance with the Saudi Building Code (SBC 201: Accessibility), reveals a need for improvements in restroom designs, door automation, and signage to better facilitate campus navigation. The results highlight the necessity for comprehensive institutional reforms, including thorough faculty training in inclusive teaching methods and Universal Design for Learning (UDL) principles, to create a truly welcoming and equitable educational environment for all students. The study concludes by stressing the potential of UDL to enhance student achievement and the importance of a holistic approach to accessibility that tackles attitudinal, technological, and physical obstacles.